2019
DOI: 10.3390/en13010083
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Early Stopping through Statistical Health Prognostic Models for Empirical RUL Estimation in Wind Turbine Main Bearing Failure Monitoring

Abstract: Details about a fault’s progression, including the remaining-useful-lifetime (RUL), are key features in monitoring, industrial operation and maintenance (O&M) planning. In order to avoid increases in O&M costs through subjective human involvement and over-conservative control strategies, this work presents models to estimate the RUL for wind turbine main bearing failures. The prediction of the RUL is estimated from a likelihood function based on concepts from prognostics and health management, and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Compared with traditional maintenance technologies, wind power intelligent O&M technology uses big data, artificial intelligence, and other technologies to manage systems more efficiently and to ensure their safety and stability through automatic monitoring and preventive measures. In addition, this O&M technology can address issues faster and more efficiently, thus reducing downtime and losses, lowering maintenance and repair costs, and improving the sustainability of wind power generation systems [105,106].…”
Section: Analysis Of Wind Power Intelligent Operation and Maintenance...mentioning
confidence: 99%
“…Compared with traditional maintenance technologies, wind power intelligent O&M technology uses big data, artificial intelligence, and other technologies to manage systems more efficiently and to ensure their safety and stability through automatic monitoring and preventive measures. In addition, this O&M technology can address issues faster and more efficiently, thus reducing downtime and losses, lowering maintenance and repair costs, and improving the sustainability of wind power generation systems [105,106].…”
Section: Analysis Of Wind Power Intelligent Operation and Maintenance...mentioning
confidence: 99%
“…A key feature in planning the industrial operation and maintenance activities is the detail of the progression of the faults along with the RUL of the equipment. Herp et al [60] presented models for the estimation of RUL of wind turbine main bearing using the likelihood functions based on the very concepts of health management, prognostics, and survival analysis. This study, after a thorough analysis of 67 different wind turbines, concluded that they discontinue functioning 13 days before their failures thereby accumulating a total of 786 days of potential non-operations.…”
Section: B Wind Power Systemsmentioning
confidence: 99%
“…From this perspective, there has been an explosion of articles since 2014 investigating the use of datadriven methods and models for the assessment of remaining useful life (RUL), as shown in Figure 1, addressing different failure prognosis techniques in the kinematic assembly, mainly in wind turbine speed reducers. Several authors [6][7][8][9][10] have used machine learning techniques or artificial neural networks (ANN) to estimate the RUL of gears and bearings in speed reducers and carry out failure prognoses. Still, the number of studies for main bearing prognosis is significantly lower [2,11], as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [12,13] employing hybrid models with deep neural networks have focused on main bearing fatigue estimates. Other studies advance the estimation of the RUL of the main bearing using natural neural network models (e.g., LSTM) [9]. The authors emphasize the need for data manipulation, data augmentation [13], and resampling [9] to estimate fatigue or RUL.…”
Section: Introductionmentioning
confidence: 99%